KARAKTERISTIK DAN SIKAP WANITA PEKERJA SEKSUAL TIDAK LANGSUNG DALAMKEIKUTSERTAAN SKRINING INFEKSI MENULAR SEKSUAL (IMS) DI KOTA SALATIGA. - Miftakhuljannah Ernestine; Rizky Amelia; Triana Sri Hardjanti (JURNAL KEBIDANAN, 2017)
Sexually Transmitted Diseases in Salatiga City is increasing from year to year. This research use correlation method with cross sectional approach. The population in this research is 54 members of paguyuban. Samples were taken by Total sampling. Test the normality of data using uju Kolmogorov SmirnovZ. The analysis used is Chi-Square analysis. The result of this research is there is a significant correlation between attitude with participation of sexually transmitted infection with p value 0,001. It is recommended that the Health Office and Puskesmas provide counseling to improve the attitude of the karaoke guide on Sexually Transmitted Infections and prevention so that the karaoke guides have a positive attitude to follow the screening activities.